RELIGIOUS DYNAMICS AND COMMUNITY RESPONSE TO AHMADIYAH IN COLO VILLAGE, DAWE DISTRICT, KUDUS - Mardiyah, Nur Maliyah Nisa; Masudi (UIN Antasari Banjarmasin, 2025)
Abstract: This research examines the community responses to religious differences within the Ahmadiyah group in Colo Village, Dawe Subdistrict, Kudus Regency. Using Glock and Stark’s theory of religious response as an analytical framework, this research employs a qualitative approach with data collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model. The findings show that some Ahmadiyah adherents in Colo Village embrace the movement due to limited ideological, doctrinal, and religious understanding, making them more receptive to new teachings. Despite theological differences, social relations between the Muslim majority and the Ahmadiyah minority remain relatively harmonious, characterized by forms of active and passive tolerance. The Ahmadiyah community maintains its existence through participation in local social activities and adaptive integration strategies. This research highlights the complexity of religious diversity and social interaction within a heterogeneous society. Keywords: Ahmadiyah; Community Response; Religious Diversity; Tolerance; Social Interaction